2015
DOI: 10.14748/ssmd.v1i2.1418
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of implants with reduced length

Abstract: INTRODUCTION:The aim of this study was to assess the reduced length implants as an alternative of conventional length implants in combination with bone augmentation. The following criteria were observed: survival rate, marginal bone loss, bleeding on probing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(2 reference statements)
1
2
1
Order By: Relevance
“…The mean survival rate of the implants placed simultaneously with split ridge osteotomy according to our methodology is 87,9%, which is lower than the survival rate of the implants placed according to other methods, which we have observed (14,15,16,17). Chiapasco et al (17,18), Sethi and Kaus(19) reported higher survival rate and their results are similar to those of Engelke et al (1).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The mean survival rate of the implants placed simultaneously with split ridge osteotomy according to our methodology is 87,9%, which is lower than the survival rate of the implants placed according to other methods, which we have observed (14,15,16,17). Chiapasco et al (17,18), Sethi and Kaus(19) reported higher survival rate and their results are similar to those of Engelke et al (1).…”
Section: Discussionsupporting
confidence: 76%
“…Chiapasco et al (17,18), Sethi and Kaus(19) reported higher survival rate and their results are similar to those of Engelke et al (1). The mean marginal bone loss is higher than the mean marginal bone loss of other methods,which were included in our study -1,586mm (14,15,16,17). Although it is lower than the marginal bone resorption described by other authors (20).…”
Section: Discussioncontrasting
confidence: 49%
“…In 1.9% up to 3% from the cases the complications required high qualification and skills for their resolution. For that reason some alternative treatment modalities could be discussed (14). There is no influence of the type of the used grafting material on the results.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma is used in a variety of clinical situations in the field of oral surgery, e.g, in the post-extraction alveoli of retained lower third molars (1,5,6).…”
Section: Introductionmentioning
confidence: 99%